Solid state photo crosslinking of plasticized starch filled with microcrystalline cellulose - Abu Bakar, Z.; Foong, J.Y.; Kahar, A.W.M.; Razak, S. (2021)
In this research, microcrystalline cellulose reinforced photo crosslinked thermoplastic starch was studied to replace petroleum-based polymers on bioplastic application. There are 3 stages in this research. The first stage will be to find the optimum formulation of microcrystalline cellulose where the variation of the amount of filler carried out in this research is 0 %, 3 %, 6 %, 9 % and 12 % of the dry weight of starch. The second stage will be to find the optimum crosslinking time using photo crosslinking where the properties of irradiated thermoplastic starch for every 0, 2, 4, 6 and 8 hours. The third stage will be to compare the properties of photo-crosslinked thermoplastic starch and peroxide crosslinked thermoplastic starch. Each formulation has undergone tensile test to study their mechanical properties and the optimum formula is obtained for subsequent studies. 6 % microcrystalline cellulose filled thermoplastic starch films was found to have the highest tensile strength and was chosen to be photo-crosslinked for the next objective. Results showed that 8 hours of photo-crosslinking time has the highest tensile strength, so this specimen is further compared with 8 hours of peroxide crosslinked specimen where peroxide crosslinked thermoplastic starch films exhibit higher tensile strength than thermoplastic starch film that is photo-crosslinked for 8 hours.